ANALISIS IMPLEMENTASI PRINSIP GOOD CORPORATE GOVERNANCE PADA PT BANK NEGARA INDONESIA (PER SERO) Tbk CABANG SURABAYA SELAMA PANDEMI COVID-19 - Rohmah, Neilly Alfiatur; Hafsah, Salvany Maulida Rahma; Kusumaningsih, Ambar; Kusumaningtias, Rohmawati (Jurnal Manajemen, 2022)
The purpose of this research is to find out and analyze the implementation of the principles of Good Corporate Governance at PT Bank Negara Indonesia (Persero) Tbk Surabaya Branch during the Covid-19 pandemic. Descriptive qualitative research methods are used by using secondary data from financial reports, websites, journals, and other literacy sources. Based on the analysis carried out, it was found that the GCG applied to Bank BNI (Persero) has been implemented properly and in accordance with the principles of transparency, accountability, independence, responsibility, and fairness during the covid-19 pandemic.